Rapid prototyping of 3D anatomical models to hemodynamic studies - Freitas, Vania (2012)
The purpose of this work is mainly to manufacture several anatomical models in a polymeric material – polydimensiloxane (PDMS) to study the blood flow through a carotid artery bifurcation. Over the last few decades, research has been shown that the geometry of the carotid artery is closely related to the development of serious cardiovascular diseases. Hence, there is a considerable interest in the development of in vitro experimental techniques able to obtain accurate measurements of the blood flow behavior through a realistic carotid artery. In this study we decide to apply rapid prototyping (RP) technologies combined with a PDMS casting technique in order to fabricate an anatomically realistic model of a human carotid to investigate, in a near future, the effect of the geometry on the local hemodynamics and consequently improve the understanding of the origin and development of these pathologies. Based on a human carotid computerized tomography (TC) it has been developed a 3D model through the application of two rapid prototyping techniques – Fused Deposition Modeling (FDM) and Tridimensional Printing (TDP). By combining the rapid prototyping techniques with a PDMS casting technique it was possible at the end to obtain an anatomically transparent model of a human carotid artery made by an elastomeric material, i.e. PDMS. Hence, we believe that this combination is a promising technique to perform in vitro blood studies through anatomically realistic models, such as a carotid artery.